52.174cm=mm

Raise m to the power of 1.

52.174cm=m1m

Raise m to the power of 1.

52.174cm=m1m1

Use the power rule aman=am+n to combine exponents.

52.174cm=m1+1

Add 1 and 1.

52.174cm=m2

52.174cm=m2

Divide each term in 52.174cm=m2 by 52.174m.

52.174cm52.174m=m252.174m

Cancel the common factor of 52.174m.

c=m252.174m

Simplify m252.174m.

Cancel the common factor of m2 and m.

Factor m out of m2.

c=m⋅m52.174m

Cancel the common factors.

Factor m out of 52.174m.

c=m⋅mm⋅52.174

Cancel the common factor.

c=m⋅mm⋅52.174

Rewrite the expression.

c=m52.174

c=m52.174

c=m52.174

Multiply by 1.

c=1m52.174

Factor 52.174 out of 52.174.

c=1m52.174(1)

Separate fractions.

c=152.174⋅m1

Divide 1 by 52.174.

c=0.01916663m1

Divide m by 1.

c=0.01916663m

c=0.01916663m

c=0.01916663m

Solve for c 52.174cm=mm